2015
DOI: 10.5709/acp-0178-7
|View full text |Cite
|
Sign up to set email alerts
|

Handwriting or Typewriting? The Influence of Penor Keyboard-Based Writing Training on Reading and Writing Performance in Preschool Children

Abstract: Digital writing devices associated with the use of computers, tablet PCs, or mobile phones are increasingly replacing writing by hand. It is, however, controversially discussed how writing modes influence reading and writing performance in children at the start of literacy. On the one hand, the easiness of typing on digital devices may accelerate reading and writing in young children, who have less developed sensory-motor skills. On the other hand, the meaningful coupling between action and perception during h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 34 publications
2
94
2
4
Order By: Relevance
“…On the one hand, the ease of typing or other supportive capabilities of digital tools are seen to be advantageous for literacy learning, particularly in children with undeveloped motor skills 35 or reading/writing difficulties 36 . On the other hand, it has been argued that the coupling of motor action and perception during handwriting can facilitate literacy acquisition, based on evidence from experimental 37 , neuroimaging 38 , and intervention studies 39 . Our data support the latter view and imply that keeping the habit of handwriting may be important for integrated mastery of higher-level literacy skills in adults.…”
Section: Multidimensionality Of Japanese Kanji Abilitiesmentioning
confidence: 99%
“…On the one hand, the ease of typing or other supportive capabilities of digital tools are seen to be advantageous for literacy learning, particularly in children with undeveloped motor skills 35 or reading/writing difficulties 36 . On the other hand, it has been argued that the coupling of motor action and perception during handwriting can facilitate literacy acquisition, based on evidence from experimental 37 , neuroimaging 38 , and intervention studies 39 . Our data support the latter view and imply that keeping the habit of handwriting may be important for integrated mastery of higher-level literacy skills in adults.…”
Section: Multidimensionality Of Japanese Kanji Abilitiesmentioning
confidence: 99%
“…Although handwriting provides added value for literacy (Longcamp, Zerbato-Poudou, & Velay, 2005), studies that address this issue from an educational perspective are few. Kindergartners tend to benefit more from handwriting training than typing training when they are subsequently asked to perform a word writing task (Kiefer et al, 2015), suggesting that handwriting is a better way than keyboarding to memorize spelling sequences at the very beginning of learning. However, the influence of low-level automaticity on writing skills has been evidenced for both handwriting and keyboarding, and a lack of fluency with a pen or keyboard leads to difficulties in text production (Beers, Mickail, Abbott, & Berninger, 2017;Graham & Harris, 2016).…”
mentioning
confidence: 99%
“…It was then suggested that reading might be affected in persons able to type but not to handwrite. However, these studies did not really address reading processes, at least at the word level (except to some extent [10]). In the present study, we took the opposite view: We decided to check whether word recognition would be modified by typing habits and we compared expert and non-expert typists in a word identification task.…”
Section: Discussionmentioning
confidence: 99%
“…Letter recognition being one of the earliest steps in word reading, motor knowledge is likely to affect skilled reading [8][9]. Beyond single letter identification, it is nonetheless still impossible to affirm that teaching typing instead of handwriting would have an effect on reading whole words (but see [10]).…”
Section: Introductionmentioning
confidence: 99%